Effect of humic acid, organic fertilization and culture date on corms production of Gladiolus x hybrida, cv. White prosperity (Latakia University Journal -Biological Sciences Series, 2024)
This research aimed to study the possibility of exploiting small cormels in the organic production of corms of the gladiolus plant in the conditions of the Syrian coast. The research was carried out in the nursery and laboratories of the Faculty of Agricultural Engineering at Tishreen University during the period (from 2021 to 2023). Humic acid at a concentration of 3 g/m2 and organic fertilizer (1 kg/m2) were used individually or jointly and on two agricultural dates: early September and mid-March.The results showed the positive effect of organic treatments on germination and vegetative indicators and quality of the resulting corms, especially the T4 treatment (humic acid and organic fertilization), which gave the best corm diameter (3.01 – 3.45 cm) and the highest corm weight (9.85-10.17 g) for the autumn and spring dates respectively.The previous treatment (T4) achieved the highest percentage of corms with a diameter greater than 2 cm resulting from planting 1 m2 (64.5, 75.9 corms/m2), The  reduction percentage of the price of the corm compared to the local market prices reached 85.22 – 87.04% for the autumn and spring dates.